Analisis perbedaan karakteristik bahan tekstil pada pembuatan busana Model Draping Cowl Neckline - Siti Aisyah; Rosmiaty Rosmiaty (Seminar Nasional LP2M UNM, 2019)
Draping is a technique of forming fabrics naturally without the help of external forces, for example, giving stitch to hold waves on the material. The ability to form materials has a direct influence on the appearance and function of the draping model on clothing. The fall of material in the draping model is determined by fiber density, woven type, fiber yarn packaging, weaving techniques and so on. The general purpose of this study is to identify the characteristics of the material for the fashion design of the draperi cowl neckline model. This research was carried out in the form of controlled experiments and involved 20 panelists, namely 5 expert panelists and 15 trained panelists to see the experimental results about the use of straight materials and rigid materials in the draperical cowl neckline model. The results showed: Suitable materials used to make cowl neckline model is satin, siffon, and shantun because it can give pleated waves well on the draperies with. Cotton cardet, cotton, organza are materials that are not suitable to use because they cannot form a draperically model maximally.